Evaluation of Hyoid Position and Retroglossal Airway After Mandibular Alveolar Archwise Distraction Osteogenesis - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2020)
The interaction between form and function in the craniofacial region is a well-accepted fact in orthodontics. The aim of the present study is to objectively evaluate if mandibular sagittal symphyseal distraction causes an increase in the retroglossal airway size and hyoid position in a retrospective clinical study. The pretreatment (T0) and 3 months post-distraction (T1) cone-beam computed tomography images of 12 patients (mean age 17.1 years) were retrieved. The retroglossal airway volume and hyoid-mandibular plane distance, hyoid-C3 distance, sella-nasion-B point angle angle, lower incisor to mandibular plane, and Mandibular plane angles were measured using 3D medical imaging software. The average amount of distraction at the superior border of the bony transport segment was 6.2 mm and 4.4 mm at the inferior border. The changes in retroglossal airway volume (2943.2 mm(3)), incisor to mandibular plane (6.5 degrees), and mandibular plane (2.1 degrees) were significant. The changes in hyoid-mandibular plane distance and hyoid-C3 distances were not significant. However, a downward repositioning in Hyoid position was observed along with the mandibular clockwise rotation. This study showed that symphyseal dentoalveolar distraction osteogenesis, as a complementary to orthodontic therapy, can affect the form and size of the pharynx. Therefore, the airway size should be one of the diagnostic and decisive factors for an ideal treatment planning.
Keywords: Alveolar distraction osteogenesis; hyoid position; retroglossal airway; symphyseal distraction; OBSTRUCTIVE SLEEP-APNEA; RAPID MAXILLARY EXPANSION; PHARYNGEAL AIRWAY; CEPHALOMETRIC EVALUATION; ELECTRICAL-STIMULATION; ORTHOGNATHIC SURGERY; ORTHOPEDIC TREATMENT; PALATAL EXPANSION; CHILDREN; DIMENSIONS